Beneficial effect of a multimerized immunoglobulin Fc in an animal model of inflammatory neuropathy (experimental autoimmune neuritis). Issue 2 (19th June 2013) - Niknami, Marzieh; Wang, Min‐Xia; Nguyen, Toan; Pollard, John D.
Abstract Intravenous immunoglobulin (IVIg) is one of the first‐line therapies for inflammatory neuropathies. Clinical use of IVIg for these disorders is limited by expense and availability. Here, we investigated a synthetic product alternative to IVIg. The aim of this study was to test the therapeutic efficacy of a novel recombinant polyvalent murine IgG2a Fc compound (stradomer™) in experimental autoimmune neuritis (EAN). Seventy‐four Lewis rats were immunized with myelin, randomized into three groups, and were treated with albumin, IVIg, or stradomer at 1% of IVIg dose. Rats were assessed clinically, electrophysiologically, and histologically. The clinical disease severity was evaluated by clinical grading and weight changes. The electrophysiological studies recorded motor conduction velocity (MCV), amplitudes, and latencies of the evoked compound muscle action potential (CMAP) and spinal somatosensory evoked potential. The treatment efficacy of the IVIg and stradomer groups was compared to the albumin (control) group. We demonstrate that stradomer has a similar therapeutic efficacy to human IVIg in EAN. Rats receiving stradomer or IVIg showed significantly lower clinical scores and less prominent weight loss compared with controls. A statistically significant improvement in both MCV and the amplitudes of distal and proximal evoked CMAP was observed in the stradomer and IVIg groups. Finally, treatment with both IVIg and stradomer resulted in statistically less inflammation and demyelinating changes in the sciatic nerve as evidenced by lower histological grade. These results reveal the potential of using fully recombinant multimerized immunoglobulin Fc instead of IVIg for treating inflammatory neuropathies.